Controlling phytoplankton blooms in a canyon-shaped drinking water reservoir via artificial and induced natural mixing: Taxonomic versus functional groups. (January 2022) - Wen, Chengcheng; Huang, Tinglin; Wen, Gang; Li, Kai; Yang, Shangye; Zhang, Haihan; Xu, Jin; Wang, Zhi
Abstract: Water-lifting aerators (WLAs) were often deployed in reservoirs to achieve artificial mixing (WLA activation) and induced (natural) mixing (early occurrence of complete natural mixing after WLA deactivation) for water quality improvement. Here, the mechanisms controlling phytoplankton growth via artificial and induced mixing were explored using a combination of taxonomic and functional classifications based on two-year monitoring data (i.e., non-operational and operational years of the WLAs). Artificial mixing resulted in a decrease of 99.2 % in phytoplankton cell density compared to that of the non-operational year, which continuously diminished to (3.06 ± 0.59) × 10 6  cells/L during induced mixing. The succession of phytoplankton structure in taxonomic and functional classification levels changed from Cyanobacteria to Chlorophyta and Bacillariophyta, from groups F, J, H1, and LM to A and X1, respectively, by comparison of the non-operational and operational years. Decreases in surface water temperature, total phosphorus concentration, and light availability, and increases in mixing depth via artificial and induced mixing were responsible for phytoplankton control, especially for cyanobacterial blooms, depending on a shift in phytoplankton composition from large or colonial, low surface to volume (S/V) to small, high S/V genera. Artificial and induced mixing also improved the trophic/ecological status of the reservoir, from "hyper-eutrophic and bad level" to "light-eutrophic and excellent level", based on an assessment of the trophic level index (TLI) and phytoplankton assemblage (Q) index. This study demonstrates that the suitable combination of artificial and induced mixing plays a crucial role in the maintenance and extension of healthy ecosystems in reservoirs. Graphical abstract: Image 1 Highlights: Algal control via artificial/induced mixing in a canyon reservoir was explored. Evaluation of algal control was performed using taxonomic/functional groups. Artificial/induced mixing drove a shift of algae with different morphology. Water temperature, total phosphorus, light and mixing depth affected algal dynamics. Artificial/induced mixing improved the trophic/ecological status of the reservoir.